2014
DOI: 10.1038/mt.2014.129
|View full text |Cite
|
Sign up to set email alerts
|

ESCRT-mediated Uptake and Degradation of Brain-targeted α-synuclein Single Chain Antibody Attenuates Neuronal Degeneration In Vivo

Abstract: Parkinson's disease and dementia with Lewy bodies are neurodegenerative disorders characterized by accumulation of α-synuclein (α-syn). Recently, single-chain fragment variables (scFVs) have been developed against individual conformational species of α-syn. Unlike more traditional monoclonal antibodies, these scFVs will not activate or be endocytosed by Fc receptors. For this study, we investigated an scFV directed against oligomeric α-syn fused to the LDL receptor-binding domain from apolipoprotein B (apoB). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 50 publications
(108 reference statements)
6
112
0
Order By: Relevance
“…These results are in agreement with our recent studies utilizing brain penetrant single chain antibodies that showed that clones capable of detecting α-syn oligomers were more effective at reducing synucleinopathy in tg when compared to single chain antibodies that had higher affinity for α-syn monomers (Spencer et al, 2014; Spencer et al, 2016). The advantage of the single chain antibodies in this study was the specificity and the ability to cross the blood brain barrier and as such they represent an important proof of principle.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in agreement with our recent studies utilizing brain penetrant single chain antibodies that showed that clones capable of detecting α-syn oligomers were more effective at reducing synucleinopathy in tg when compared to single chain antibodies that had higher affinity for α-syn monomers (Spencer et al, 2014; Spencer et al, 2016). The advantage of the single chain antibodies in this study was the specificity and the ability to cross the blood brain barrier and as such they represent an important proof of principle.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we developed single chain antibodies targeting α-syn oligomers and fibrils expressed from lentiviral vectors (Price et al, 2016; Spencer et al, 2014; Spencer et al, 2016). Although promising, there were some limitations, which led to the development of highly specific monoclonal antibodies differentially targeting oligomers versus fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…The expressions of the striatal Tlr2 and the α-synuclein accumulation were also decreased by injection of LV-sh.TLR2 (data not shown). The α-Syn tg mice showed astrogliosis and microglia activation (Kim et al, 2013; Spencer et al, 2014), and delivery of LV-sh.TLR2 significantly decreased both microglia activation and astrogliosis in this model (Figures 4A, 4D, and 4E). Similar to our previous results, immunohistochemical analysis showed that expression of Tlr2 was increased in the α-Syn tg mice compared to non-tg mice (Kim et al, 2013) (Figures 4A, 4B, and S4D).…”
Section: Resultsmentioning
confidence: 99%
“…scFvs retain antigen-binding properties and can be easily screened for desired affinities using phage display methodology. Using this type of approach, scFvs that detect individual conformational species of α-syn have been identified [151][152][153], and could be potentially used to discriminate among protein conformers for the differential treatment of synucleinopathies or for diagnostic purposes [154]. Moreover, scFvs can be further modified to increase BBB penetrability and facilitate the clearance of α-syn.…”
Section: Developing New Technologies For Immunotherapymentioning
confidence: 99%
“…In this sense, a fusion protein comprising a scFv against α-syn plus the low density lipoprotein domain of apolipoprotein B was recently studied in a transgenic model of DLB. The braintargeted fusion antibody easily crosses the BBB and gets internalized by neurons using the endosomal sorting complexes required for transport (ESCRT) pathway for enhanced degradation of α-syn aggregates [151], thus attenuating neuronal degeneration in vivo. Similarly, a fusion protein comprising a scFv and a specific protease can further aid in the clearance of aggregation-prone proteins [155].…”
Section: Developing New Technologies For Immunotherapymentioning
confidence: 99%